2018
DOI: 10.1183/13993003.02238-2017
|View full text |Cite
|
Sign up to set email alerts
|

Chronic breathlessness: re-thinking the symptom

Abstract: Is chronic breathlessness a symptom or a syndrome? Although hotly debated [1-5], we would like to suggest an alternative viewpoint. Here, we speculate that the argument over chronic breathlessness being considered as either a symptom or syndrome both holds us within a reductionist framework, and somewhat misses the point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…14 These findings have been interpreted according to the Bayesian model, and some authors suggest that training can improve accuracy by decreasing the error predictions 32 or by improving expectations related to body signals. 16 The same explanation applies to the improved interoception as assessed by the MAIA in dancers. Professional dancers are given extensive training in detecting and modulating their body states.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…14 These findings have been interpreted according to the Bayesian model, and some authors suggest that training can improve accuracy by decreasing the error predictions 32 or by improving expectations related to body signals. 16 The same explanation applies to the improved interoception as assessed by the MAIA in dancers. Professional dancers are given extensive training in detecting and modulating their body states.…”
Section: Discussionmentioning
confidence: 92%
“…22 Studies have reported that long-term dance training is related to changes in several physical parameters (eg, fitness, flexibility, range of motion, and balance 2,13 ), in neurocognitive motor control (eg, movement timing, visual and motor imagery 5 ), in pain mechanisms (eg, greater activity of the descending inhibitory system 18 ), and in brain function and structure. 7,22 The effects of training/learning on various aspects of perception and communication of subjective body states was demonstrated in other interoception modalities, 16 in the MAIA self-regulation subscale, 6,11 and in several diseases. 3,8 Our previous study demonstrated that the variability of pain reports was reduced with training and that the placebo response was lower in the trained subjects than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…100 However, prior experiences, expectations and individual psychology do impact on the effect of breathlessness, much like the feeling of pain. 101 Parallels with pain are also notable in studies that show that vicarious dyspnoea (breathlessness) can be induced in empathetic individuals watching others struggling to breathe. 102 Breathlessness thus offers distinct challenges for those attempting to measure it.…”
Section: Measurement Mattersmentioning
confidence: 99%
“…Various groups have studied the use of counselling, coaching and goal setting after PR, generally showing small improvements in physical activity. 34 , 35 The barriers and enablers to increasing physical activity for people living with COPD are complex and varied, including physical, environmental and psychosocial factors.…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%
“…The Breathe Oxford group argue that this is beyond the complicated pathophysiology, incorporating prior experiences and expectations as well as the personal perception of body signals. 35 Most PR programmes include an educational component usually concentrating on self-management, including how to manage breathlessness, medication adherence, inhaler technique, action plans for exacerbations and nutrition, as well as promotion of mental health and facilitation of advanced care plans. Delivered as education, they are by definition health-professional-centred, and in terms of sustained behavioural change, their effectiveness is variable.…”
Section: Copd and Pulmonary Rehabilitation: The Psychosocial Dimensiomentioning
confidence: 99%